Library usage of medical students: a comparative analysis of first year and third year students in Universiti Putra Malaysia - Sahak, Mohd Dasuki; Masrek, Mohamad Noorman (Elsevier, 2014)
The rapid proliferation of information in the present era has important implications for the education and library usage of health professionals including medical students. The purpose of this study is to investigate the usage of library resources among first and third year medical students in the Faculty of Medicine and Health Sciences (FPSK), Universiti Putra Malaysia (UPM) from July 2009 until April 2010. Adopting a survey research methodology involving 205 students, the findings suggest that the three mostly used library resources are the Internet, newspaper and library websites while the three mostly used facilities are computer, reading area and discussion room. In addition, it is also found that there is no significant difference between male and female in most of the resources usage. In contrast, significant difference could be observed between Year1 and Year 3 in most of the resources usage. The significance of the study could be assessed from both theoretical and practical perspective.